Three Stories - Tomislav Kuzmanović; Senko Karuza ([sic])
It’s summer and the beer keeps flowing down our throats, the music echoes from a club and every now and then we walk out on the terrace to catch a breath of air free of smoke, to meet someone and start something new, and if it doesn’t happen, we go back inside and shake at the dance floor, at the bar. And when we get bored, we walk out again and look from someone.We give up before the end, before sunrise, because we cannot stand the dawn that will reveal our impotence, we stumble and laugh along as if we’ve won a trip to the heavens in which no one lives, we give everything we’ve got to remain in this good trance, we imagine what we’d do if she weren’t such a cow that got hooked on that good-for-nothing, and, after all, don’t you think good girls always end up with the likes of him, we’ll never understand it. Comfort is good, but not good enough to put an end to this night, to peacefully collapse into our bed next to the open window and fall asleep as if love exists, and tonight we just didn’t get lucky.